2020
DOI: 10.36941/ajis-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Majority Shareholder on the Composition of Public Ownership and Tax Avoidance Practices in Public Companies

Abstract: This study attempts to analyze the effectiveness of the enforcement of regulations on public share ownership. Specifically, this study analyzes whether there are differences in the composition of public ownership between before and after the regulation was enacted. By using independent t-test, carried out on the Indonesia Stock Exchange during 2008-2011 with a total of 320 observations (company-years), regarding the effectiveness of regulations regarding the provision of tax incentives associated with the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…However, other findings indicate that high public ownership increases companies' likelihood of tax avoidance (Alexander, 2019;Bauwhede et al, 2003). Contrary to these two groups of findings, Iqbal et al (2020) research failed to prove the relationship between public ownership and tax avoidance. This research can be a starting point for further research on public ownership in public companies' tax evasion practices in Indonesia.…”
Section: Introductionmentioning
confidence: 69%
“…However, other findings indicate that high public ownership increases companies' likelihood of tax avoidance (Alexander, 2019;Bauwhede et al, 2003). Contrary to these two groups of findings, Iqbal et al (2020) research failed to prove the relationship between public ownership and tax avoidance. This research can be a starting point for further research on public ownership in public companies' tax evasion practices in Indonesia.…”
Section: Introductionmentioning
confidence: 69%
“…Fisher [11] found that role ambiguity has a significant negative effect on job performance and auditor job satisfaction. Iqbal et al [12] show that role ambiguity has no significant effect on auditor performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…According to the legislative authorities, taxes are considered compulsory government contributions rather than voluntary payments or donations. Nowadays, more focus is being given to the characteristics of economic systems in the race for a globalized international environment in achieving potentially more prosperous economic goals (Iqbal et al, 2020). Although each country's tax system has separate economic regulations accordingly, countries develop their own appropriate system for the economy.…”
Section: Taxationmentioning
confidence: 99%
“…Tax reduction advocates contend that lower tax rates encourage saving, investing, and productive work and have an effect on a nation's economic growth (Ferede & Dahlby, 2012). For example, the studies by Iqbal et al (2020) and Iram et al (2020) show different results in economic growth as a consequence of the change in taxes. In evaluating the tax revenue systems of India and Pakistan from 1999-2000to 2008-2009, Aamir et al (2011 conducted an extensive study.…”
Section: Review Of Literaturementioning
confidence: 99%